If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -6 = 8m Reorder the terms: -6 + 2m = 8m Solving -6 + 2m = 8m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8m' to each side of the equation. -6 + 2m + -8m = 8m + -8m Combine like terms: 2m + -8m = -6m -6 + -6m = 8m + -8m Combine like terms: 8m + -8m = 0 -6 + -6m = 0 Add '6' to each side of the equation. -6 + 6 + -6m = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -6m = 0 + 6 -6m = 0 + 6 Combine like terms: 0 + 6 = 6 -6m = 6 Divide each side by '-6'. m = -1 Simplifying m = -1
| 3(4m-6)=18 | | x+4(x-6)=2(x-2)-23 | | 36x^2+48x-16= | | 20x+16-27=5x-1 | | .5(x-2)=9 | | 7x-84=3x | | x^3+4x^2+8x=0 | | 4+2(x+5)=-2 | | 2-(4x+7)=4(x-1) | | X-15=23 | | 16b^2-40b+25= | | 3a+2b=6 | | 17=x+1 | | (2x-5)*(x^2-3x+2)=0 | | ln(x-1)=ln(x+5) | | 3c=2(c-1) | | 2(7s+9)-8s=2(3s+2)-6 | | -1(y)-1=(3x+2) | | 12(x+2)=3(4x+3)+15 | | 1/4(x-8)+1/2(x+2)=x-3 | | 12x+6y=100 | | 1(y)=1(3x+7) | | x^2+6x+36=51 | | 12(3x+5)-5(2x-6)=6x-30 | | 0.25(y+3)=7 | | 16x^2+32x+13=0 | | 9k-7=-25 | | 5-(-4s+2)=13 | | X-Y=z | | (10x-13)=(6x+1) | | (10x-7)=5x(4x+6) | | (10x-7)=(4x+6) |